Pertumbuhan, Kandungan Klorofil dan Serat Kasar pada Defoliasi Pertama Alfalfa (Medicago sativa L ) Akibat Pemupukan Mikorisa - Parman, Sarjana; Harnina, S. (BULETIN ANATOMI DAN FISIOLOGI dh SELLULA, 2008)
Research about growth, chlorophyl and fibre content at first defoliation in alfalfa (Medicago sativa L)after giving biofertilizer mycorrhiza have been done.. This research beginning at 15 March 2006 – 15agustus 2006 in research on biological garden FPMIPA UNNES Semarang, using plastic polybag, anddesign research of complete randomized design, one treatment that is give of mycorriza with fiveconcentration that is Mo ( without mikorizzsa); M1 ( ½ capcule/plant ; M2 ( 1 capcule/plant), M3 ( ofmikorizza 11/2 capcule/plant) and M4 ( 2 capcule/plant). Every treatment repeating 5 times. Chlorophyllcontent determined to use method Arnon ( 1949 in Hukmani & Tripathy, 1994); Fibre content used bymethod AOC ( 1970 in Sudarmaji, 1984 data analyzed this research by computer with SPSS-13 program.Result of research show there are high difference of plant , sum of dry weight and of alfalfa at firstdefoliation. So the chlorophyll content is ( mg/100 gram naterial) is M0 ( 158,94), M1 ( 149,15), M2 (202,12), M3 ( 208,69) and M4 ( 196,91) is sigmificant at p=0,007. Contain average fibre of alfalfa do notsignifikan ( p=0,067) start from M0 ( 26,42), M1 ( 26,11), M2 ( 29,57), M3 ( 22,55) and M4 ( 23,44).Conclusion from this research that mycorrhiza biofertilizer influence growth, but not have an in with highdry weight and crop of plant crop, and able to improve content of chlorophyll of crop and have an effect onin is not real at improvement of harsh fibre of alfalfa ( M. sativa L). At first defoliasi of crop M. sativaL.